Heparosan‐Derived Heparan Sulfate/Heparin‐Like Compounds: One Kind of Potential Therapeutic Agents. Issue 3 (11th April 2012) - Li, Pingli; Sheng, Juzheng; Liu, Yuhong; Li, Juan; Liu, Jian; Wang, Fengshan
Abstract Heparan sulfate (HS) is a highly sulfated glycosaminoglycan and exists in all animal tissues. HS and heparin are very similar, except that heparin has higher level of sulfation and higher content of iduronic acid. Despite the fact that it is a century‐old drug, heparin remains as a top choice for treating thrombotic disorders. Pharmaceutical heparin is derived from porcine intestine or bovine lung via a long supply chain. This supply chain is vulnerable to the contamination of animal pathogens. Therefore, new methods for manufacturing heparin or heparin‐like substances devoid of animal tissues have been explored by many researchers, among which, modifications of heparosan, the capsular polysaccharide of Escherichia coli K5 strain, is one of the promising approaches. Heparosan has a structure similar to unmodified backbone of natural HS and heparin. It is feasible to obtain HS or heparin derivatives by modifying heparosan with chemical or enzymatic methods. These derivatives display different biological activities, such as anticoagulant, anti‐inflammatory, anticancer, and antiviral activities. This review focuses on the recent studies of synthesis, activity, and structure‐activity relationship of HS/heparin‐like derivatives prepared from heparosan.